Harnessing marine microorganisms in the battle against the influenza virus - Rezmer, Jakub; Wasilewska, Inga; Homa, Wojciech; Wanat, Joanna; Kobiernik, Adam; Fortuniak, Weronika (Journal of Education, Health and Sport, 2025)
The Orthomyxoviridae family of RNA viruses is responsible for influenza. Both influenza A and B strains induce seasonal influenza illnesses, whereas influenza C typically only results in minor respiratory sickness. Coughing and sneezing can spread the disease, and direct touch can transmit the virus. Although a few authorized anti-influenza drugs accessible such as oseltamivir, amantadine, and rimantadine, are available, due to the expanding drug resistance, they are becoming less efficient and effective. Microorganisms living in the marine environment can produce unique chemical compounds with potent biological activity, including antiviral. Natural antiviral substances can be used against various viruses pathogenic to humans, including influenza. This review aimed to search for potential anti-influenza properties of different substances derived from marine microorganisms. The literature review was conducted using the PubMed scientific database. The authors propose a great variety of substances that could be potentially helpful in the fight against influenza. Starting from abyssomycins, polysaccharides, and spirostaphylotrichin, through violapyrones, polyketides indole diterpenoids, finishing with microalgae and cyanobacteria extracts and others. Some of them directly target the viral adsorption and internalization processes, inhibit viral polymerase activity, or stimulate the immune system of the host. In the future, potential drugs that could be used to improve the treatment of influenza are believed to be obtained from marine sources, which could be used for the creation of innovative pharmaceuticals. The authors of the studies strongly advise additional in vitro and in vivo research on substances with potential antiviral properties.